Pemodelan Integration Use Case (IUC): Perancangan Use Case Diagram (UML) untuk Sistem-sistem yang Terintegrasi - Rospricilia, Tita Ayu; Ma'ady, Mochamad Nizar Palefi (INTEGER: Journal of Information Technology, 2024)
Modeling use cases in software development for a system has been well-documented in literature. Today, digital business competition is becoming faster and more integrated. System or software development now not only analyzes the development of the system itself but also considers how the system can later be integrated with other systems or features in other companies' applications. Therefore, designing use case diagrams for integrated systems has become important; however, based on the author's observations, literature discussing this is still very limited. This article aims to identify and to explain the modeling of integration use cases (IUC) through discussions in the case study of school information system management, as well as to educate readers on the importance of IUC based on the correct and proper use of UML notation. This article discusses in detail the fundamental understanding of notations in depicting use case diagrams, the creation of integration use case diagrams (IUCD) for systems integrated with existing and new systems.